Defective Bimetallic Selenides for Selective CO2 Electroreduction to CO. Issue 3 (2nd December 2021) - Wang, Jiajun; Zheng, Xuerong; Wang, Guangjin; Cao, Yanhui; Ding, Wenlong; Zhang, Jinfeng; Wu, Han; Ding, Jia; Hu, Huilin; Han, Xiaopeng; Ma, Tianyi; Deng, Yida; et al.
Abstract: CO2 electroreduction (CO2 RR) to CO is promising for the carbon cycle but still remains challenging. Au is regarded as the most selective catalyst for CO2 RR, but its high cost significantly hinders its industrial application. Herein, the bimetallic CuInSe2 is found to exhibit an Au‐like catalytic feature: i) the interaction of Cu and In orbitals induces a moderate adsorption strength of CO2 RR intermediates and favors the reaction pathway; and ii) the hydrogen evolution is energetically unfavorable on CuInSe2, as a surface reconstruction along with high energy change will occur after hydrogen adsorption. Furthermore, the Se vacancy is found to induce an electron redistribution, slightly tune the band structure, and optimize the CO2 RR route of bimetallic selenide. Consequently, the Se‐defective CuInSe2 (V‐CuInSe2 ) achieves a highly selective CO production ability that is comparable to noble metals in aqueous electrolyte, and the V‐CuInSe2 cathode shows a satisfactory performance in an aqueous Zn–CO2 cell. This work demonstrates that designing cost‐effective catalysts with noble‐metal‐like properties is an ideal strategy for developing efficient electrocatalysts. Moreover, the class of transition bimetallic selenides has shown promising prospects as active and cost‐effective electrocatalysts owing to their unique structural, electronic, and catalytic properties. Abstract : Bimetallic CuInSe2 with Se vacanies (V‐CuInSe2 ) significantly optimizes the adsorption of CO2 electroreduction intermediates owing to its moderate band center relative to the Fermi level. Meanwhile, hydrogen evolution is suppressed on V‐CuInSe2 due to an energetically unfavorable surface reconstruction after hydrogen adsorption. Consequently, the V‐CuInSe2 achieves a highly active and selective CO generation ability.